PENGARUH FASILITAS DAN HARGA PADA MINAT BERKUNJUNG DI PANTAI LON MALANG SAMPANG - Khairul Huda; Yustina Chrismardani (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2023)
The motivation behind this awareness is to find out the effect of prices and facilities on visiting intentions. People who know or have heard in the last 1 year. With a population of 100 respondents with a purposive sampling method. Methods of data collection is done by distributing questionnaires, this research is quantitative. The analytical methods in this study are instrument test (validity and reliability), classic assumption test, multiple linear regression analysis and t test, F test, and test of the coefficient of determination. The results of this study indicate (1) facilities have a significant effect on visiting intentions, (2) prices have a significant effect on visiting intentions, (3) facilities and prices have a significant effect on visiting intentions.